Expanding Tactics for Listening. More Listening. More Testing. More Effective: Teacher's Book - Richards J. C. Jack (Oxford, Oxford University Press, 2011)
More listening. More testing. More effective. Tactics for Listening Third Edition is a three-level listening series featuring Jack Richards' practical-English methodology and easy-to-teach format. The series has been comprehensively revised and expanded to provide more listening input and a new focus on developing test-taking skills. TEACHER'S BOOK INCLUDES: Lesson plans. Answer keys. Optional activities. Vocabulary lists. Audio scripts. Vocabulary Worksheets. TESTING PROGRAM & RESOURCE CD-ROM INCLUDES: Unit quizzes. General midterm and final tests. Midterm and final tests in the style of the TOEIC® test and other exams. Conversation Worksheets. Answer keys for the Vocabulary and Conversation Worksheets